Reaction of 3-hydrazone-5,6-Diphenyl-1,2,4-Triazines with Various Activating Agents - Abdel-Rahman, R.M.; Seada, M.; Fawzy, M.M.; El-Baz, Ibrahim (Asian Journal of Chemistry, 2010)
The reaction of 3-hydrazone-5,6-diphenyl-1,2,4-triazines(III) with various activating agents such as bases, chalcones, acrylonitrile, maleic anhydride, bromine, phenylmagnesium bromide acid halides and reduction with zinc in acetic acid have been studied. Spectroscopic data are given in support of the structure of the products.